Aplicación Móvil para Mejorar los Procesos de Enseñanza Aprendizaje de los Niños con Sindrome de Down y Austismo de la Escuela de Educacion Especial “Ayudanos A Empezar” de la Ciudad de Babahoyo - Zamora Millan, Jonathan Javier (2018)
The present work is aimed at analyzing the way in which they are taught knowledge in the special education school "Help us start", to children with Down syndrome and Autism, to be able to make the proposal for the elaboration of a mobile application for the Android operating system, which will help in the methods of teaching-learning and will seek to capture the attention of children so that they receive a interactive education that improves their motivation to learn and in this way through methods playful keep their minds awake and attentive to receive knowledge. During the development of this work, we will work in collaboration with the teachers of the educational institution to be able to collect the necessary information for the development of a application that is capable of capturing children's attention in order to fulfill the objective of have their attention and that they can learn effectively, in addition, the tests are planned necessary with the children in order to finally deliver an optimal application that Comply with the teaching requirements. The application does not pretend to be a definitive method for teaching, but its objective is be a complement through which children can put their knowledge into practice to be able to reinforce or improve them if necessary, because currently with the growing emergence of technology, the world requires us to be people with knowledge in the use of same, for this reason we see ourselves in the task of being inclusive with children with Down and Autism because they need other methods to learn how to make use of different technologies and the tools they offer us.